Estudo de associação entre os polimorfismos dos genes da POMC, MC4R, HMCN-1 e COMT e a suscetibilidade à depressão pós-parto - Antonio Marcos Alvim Soares Junior (2012)
Postpartum depression is a common disorder affecting women, with important consequences for both mother and child. A genetic determinant for PPD is suggested by many genetic epidemiologic studies. One hundred and seventeen women subjects were randomly selected among those who delivered in a maternity hospital and filled in the Edinburgh Postpartum Depression Scale (EPDS) questionnaire and a structured psychiatric interview (MINI PLUS 5.0), about 8 weeks after delivery. POMC, MC4-R, HMCN-1 and COMT polymorphisms were analysed by PCR.Differences in genotype frequency were calculated by X2 test and the difference between groups was tested with Students t test. Tests were two-tailed and results significant when p !0.05. Following the psychiatric structured interview 34 (29,06%) women were diagnosed with PPD. No significant statistical differences in terms of socio-demographic data were observed between depressed (PPD+) and non-depressed women (PPD-) except for educational level. No differences in POMC and MC4R genotype distribution were observed between the depressed and non-depressed women. We found a significant interaction between the development of depressive symptoms in postpartum and olymorphisms in HMCN-1 (p ! 0.01) and COMT (p=0,01). In conclusion, this study supports the notion that PPD is the result of complex interactions between multiple variables, including genetic factors. It is encouraged independent replications in larger samples and further investigation on these gene effects in PPD.